2021
DOI: 10.1007/s00259-021-05271-w
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study to assess safety, biodistribution and radiation dosimetry for 89Zr-girentuximab in patients with renal cell carcinoma

Abstract: Purpose In this phase I study, we evaluated the safety, biodistribution and dosimetry of [89Zr]Zr-DFO-girentuximab (89Zr-girentuximab) PET/CT imaging in patients with suspicion of clear cell renal cell carcinoma (ccRCC). Methods Ten eligible patients received an intravenous administration of 37 MBq (± 10%) of 89Zr-girentuximab at mass doses of 5 mg or 10 mg. Safety was evaluated according to the NCI CTCAE (version 4.03). Biodistribution and normal organ do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Its preliminary results were reported recently, and exceed the predetermined sensitivity and specificity study targets, with the imaging agent delivering 86% sensitivity and 87% specificity [46]. The phase I study showed in all ten cases a good toxicity profile, and was able to differentiate between clear-cell RCC and non-clear-cell RCC renal mass [47]. This technology is also being examined for diagnostic and therapeutic purposes in the STARLITE 2 Phase II study which evaluates the efficacy of Lu177 conjugated to girentuximab + nivolumab (anti-PD-1) systemic therapy.…”
Section: I-cg250 ( 124 I-girentuximab)mentioning
confidence: 85%
“…Its preliminary results were reported recently, and exceed the predetermined sensitivity and specificity study targets, with the imaging agent delivering 86% sensitivity and 87% specificity [46]. The phase I study showed in all ten cases a good toxicity profile, and was able to differentiate between clear-cell RCC and non-clear-cell RCC renal mass [47]. This technology is also being examined for diagnostic and therapeutic purposes in the STARLITE 2 Phase II study which evaluates the efficacy of Lu177 conjugated to girentuximab + nivolumab (anti-PD-1) systemic therapy.…”
Section: I-cg250 ( 124 I-girentuximab)mentioning
confidence: 85%
“…The biodistribution is similar to that of other [ 89 Zr]-mAb with a slow clearance from liver, heart, kidney and blood pool. The uptake from renal cell carninoma (assumed to be hypoxic) is rather slow in the clinical trial performed by Merkx et al ( 156 ).…”
Section: Medical Imagingmentioning
confidence: 99%
“…CAIX is overexpressed in clear-cell renal-cell tumors (ccRCC) due to a mutation in the Von Hippel-Lindau protein [41]. A number of biodistribution studies have evaluated 89 Zr-labeled girentuximab, an anti-CAIX monoclonal antibody [42][43][44]. These studies have shown 89 Zr-girentuximab was safe and allowed differentiation between ccRCC and non-ccRCC lesions, enabling early detection of tumor recurrence and inform clinical decision making (Figure 2).…”
Section: Caixmentioning
confidence: 99%